RobotChain: Artificial Intelligence on a Blockchain using Tezos Technology - Lopes, Vasco Ferrinho (2020)
Blockchain technology is not only growing everyday at a fast-passed rhythm, but it is also a disruptive technology that has changed how we look at financial transactions. By providing a way to trust an unknown network and by allowing us to conduct transactions without the need for a central authority, blockchain has grown exponentially. Moreover, blockchain also provides decentralization of the data, immutability, accessibility, non-repudiation and irreversibility properties that makes this technology a must in many industries. But, even thought blockchain provides interesting properties, it has not been extensively used outside the financial scope. Similarly, robots have been increasingly used in factories to automate tasks that range from picking objects, to transporting them and also to work collaboratively with humans to perform complex tasks. It is important to enforce that robots act between legal and moral boundaries and that their events and data are securely stored and auditable. This rarely happens, as robots are programmed to do a specific task without certainty that that task will always be performed correctly and their data is either locally stored, without security measures, or disregarded. This means that the data, especially logs, can be altered, which means that robots and manufacturers can be accused of problems that they did not cause. Henceforth, in this work, we sought to integrate blockchain with robotics with the goal to provide enhanced security to robots, to the data and to leverage artificial intelligence algorithms. By doing an extensive overview of the methods that integrate blockchain and artificial intelligence or robotics, we found that this is a growing field but there is a lack of proposals that try to improve robotic systems by using blockchain. It was also clear that most of the existing proposals that integrate artificial intelligence and blockchain, are focused on building marketplaces and only use the latter to storage transactions. So, in this document, we proposed three different methods that use blockchain to solve different problems associated with robots. The first one is a method to securely store robot logs in a blockchain by using smart-contracts as storage and automatically detect when anomalies occur in a robot by using the data contained in the blockchain and a smart-contract. By using smart-contracts, it is assured that the data is secure and immutable as long as the blockchain has enough peers to participate in the consensus process. The second method goes beyond registering events to also register information about external sensors, like a camera, and by using smart-contracts to allow Oracles to interact with the blockchain, it was possible to leverage image analysis algorithms that can detect the presence of material to be picked. This information is then inserted into a smart-contract that automatically defines the movement that a robot should have, regarding the number of materials present to be picked. The third proposal is a method that uses blockchain to store information about the robots and the images derived from a Kinect. This information is then used by Oracles that check if there is any person located inside a robot workspace. If there is any, this information is stored and different Oracles try to identify the person. Then, a smart-contract acts appropriately by changing or even stopping the robot depending on the identity of the person and if the person is located inside the warning or the critical zone surrounding the robot. With this work, we show how blockchain can be used in robotic environments and how it can beneficial in contexts where multi-party cooperation, security, and decentralization of the data is essential. We also show how Oracles can interact with the blockchain and distributively cooperate to leverage artificial intelligence algorithms to perform analysis in the data that allow us to detect robotic anomalies, material in images and the presence of people. We also show that smart-contracts can be used to perform more tasks than just serve the purpose of automatically do monetary transactions. The proposed architectures are modular and can be used in multiple contexts such as in manufacturing, network control, robot control, and others since they are easy to integrate, adapt, maintain and extend to new domains. We expect that the intersection of blockchain and robotics will shape part of the future of robotics once blockchain is more widely used and easy to integrate. This integration will be very prominent in tasks where robots need to behave under certain constraints, in swarm robotics due to the fact that blockchain offers global information and in factories because the actions undertaken by a robot can easily be extended to the rest of the robots by using smart-contracts.